Epidemiological trends and age-period-cohort effects on subarachnoid hemorrhage burden across the BRICS-plus from 1992 to 2021 - Liang Guo; Liang Guo; Liang Guo; Liang Guo; Liang Guo; Dan Song; Dan Song; Dan Song; Dan Song; Dan Song; Li Chen; Li Chen; et al. (Frontiers in Medicine)
BackgroundSubarachnoid hemorrhage (SAH) is a major global health concern associated with disproportionately high morbidity and mortality. The BRICS-plus nations (Brazil, Russian Federation, India, China, South Africa, and six other new members), account for a substantial proportion of the global population while being confronted with distinct public health challenges. This study aims to examine epidemiological trends and regional variations in SAH burden across BRICS-plus nations through comprehensive and timely analysis.MethodsData on the number, all-age rate, age-standardized rate, and relative change in SAH incidence from 1992 to 2021 across eleven BRICS-plus members were sourced from the Global Burden of Disease Study (GBD) 2021. Associations between the incidence rate and the Socio-demographic Index (SDI) were assessed through Pearson correlation analyses. Furthermore, age-period-cohort modeling was utilized to quantify net drift, local drift, age, period, and cohort effects over the past three decades.ResultsExcept for China, SAH cases were observed to have significantly increased in the other ten BRICS members from 1992 to 2021. All BRICS-plus countries exhibited a declining trend in the age-standardized incidence rate over the study period. Indonesia reported the highest age-standardized incidence rate (10.94 per 100,000 population) in 2021, while China displayed the most significant decrease, at 59.36%. The annual net drift in the SAH incidence rate ranged from −3.36%% for China to −0.50% for the Russian Federation among the eleven countries. A significant negative correlation was observed between the incidence rate of SAH and SDI values. Nations displayed similar age-effect patterns characterized by initial declines followed by subsequent increases with advancing age, along with distinct period and cohort effects that may reflect variations in control measures and temporal burden patterns.ConclusionOur study demonstrates the overall decline in age standardized incidence rate of SAH, while highlighting the persistent health inequalities among eleven countries potentially attributable to socioeconomic disparities. Furthermore, the findings underscore the imperative for tailored interventions across age, period, and cohort dimensions to mitigate SAH-specific challenges in nations undergoing rapid development.